Permasalahan Terkait Obat pada Pasien Skizofrenia Rawat Inap: Tinjauan Sistematik Mengenai Prevalensi dan Intervensi - Salma Auliya Fatimah; Woro Harjaningsih; Bambang Hasta Yoga Legawa Budiman; Fivy Kurniawati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Schizophrenia is a severe mental disorder with increasing prevalence. Treatment for schizophrenia is chronic and often leads to Drug-Related Problems (DRPs), especially in hospitalized schizophrenia patients. This systematic review aims to map the prevalence and most common types of DRPs and evaluate the impact of clinical pharmacist involvement in addressing DRPs. A literature search was conducted across six electronic databases (Scopus, PubMed, ScienceDirect, Web of Science, ProQuest, and Springer Nature) for publications published between January 2009 and December 2024. Eleven studies met the inclusion criteria, consisting of nine cross-sectional studies and two quasi-experimental studies, with a total of over 61,000 hospitalized schizophrenia patients. The prevalence of DRPs has been reported to range from 52.8% to 100%, depending on the study design and the DRP identification method. Studies using structured medication reviews reported a higher DRP burden, at 0.75–2.5 DRPs per patient. The most frequently identified types of DRPs include polypharmacy, drug interactions, inappropriate medication selection, and dosing problems (overdose and underdose). QTc prolongation was reported in 2.5–8.26% of patients. Clinical pharmacist involvement was reported in three studies, with physician acceptance of recommendations ranging from 49 to 50%. DRPs are a common problem in hospitalized patients with schizophrenia, and clinical pharmacist involvement has the potential to improve the rationality and safety of drug therapy.